Meat industry by-products: a bio-refinery approach to the production of safe, value added products for sustainable agriculture applications - Woodgate, Stephen L. (Frontiers in Animal Science, 2023)
This mini-review review examines the role of animal by-products (ABP), produced by the process known as rendering. It explains how the use of rendered products has evolved and changed over the last 50 years and how the bovine spongiform encephalopathy (BSE) epidemic in the UK and the rest of Europe challenged the survival of the industry. The subsequent changes to the rendering industry resulting from BSE are described by way of key research and regulatory changes. As a result of the developments in the modern rendering industry, it has evolved into an important component of the current human food chain. The role of the rendering industry in producing a wide range of safe, high quality, sustainable products from ABP materials is explored.